Expressão imunocitoquímica dupla de p16 e ki67 em amostras de exame citológico cérvico-vaginal em base líquida comparada com achados da citologia, biópsia e teste de captura híbrida para HPV: um estudo de acurácia diagnóstica - Prigenzi, Karla Calaca Kabbach [UNIFESP] (2019)
Objective: To evaluate the acuracy of the dual immunocytochemistry staining for p16 and Ki67 in liquid-based cytology samples for cervical and vaginal lesions screening, compared to biopsy findings and HPV-DNA molecular detection. Methods: Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values for the dual immunocytochemistry assay for p16 and Ki67 expression detection were calculated in comparison with histopathological results and to high-risk HPV-DNA detection. Results: 198 women were included randomly, aged 32.3 years (standard deviation, SD, 8.3). The majority (96.2%) of those with negative dual assay results had lower biopsy grades (p < 0.001). Women with cytology results suggestive of ASC-H (atypical squamous cells - high grade) or HSIL (high-grade squamous intraepithelial lesion) had positive dual immunocytochemistry assay results more frequently (p < 0.001), and these positive results were also significantly associated with biopsy findings of intraepithelial neoplasia grade 2 (IN-2) or higher (p < 0.001) and with high-risk genotype HPV infection (p = 0.003). Specificity and PPV of the dual assay were 0.927 (0.849-0.973) and 0.625 (0.354-0,848) respectively, for detection of IN-2 or more; and for the HPV test, the sensibility and NPV for detection of IN-2 or higher were 0.937 (0.697-0.998) and 0.888 (0.517-0.997). Conclusion(s): This study showed that the dual immunocytochemistry assay can be incorporated into cervical cancer screening, using a single liquid-based cytology sample. As it reveals a persistent HPV infection, it reliably refers patients to colposcopy therefore avoiding unnecessary procedures when it shows negative results. The dual assay had high specificity and PPV for the detection of IN-2 or higher compared to high-risk HPV-DNA detection.